Cancer strigosus Linnaeus, 1760: neotype selection, its identification with Cancer cancharus Linnaeus, 1758, and reversal of precedence (Crustacea: Decapoda: Galatheidae) - Ahyong, Shane T.; Tan, Swee Hee; Low, Martyn E. Y.; Macpherson, Enrique (Zootaxa, 2017)
The squat lobster Galathea strigosa (Linnaeus, 1760) (Galatheidae) was first described as Cancer strigosus by Linnaeus (1760: 495) from material collected by A. Martin “in Mari Norvegico” (Norwegian Seas) (inadvertently indicated in error as “southern Devon, England” by Baba et al. 2008). The species is widely-distributed in the northeastern Atlantic including the Mediterranean Sea and the name is in current and prevailing usage (see references cited below); it is also the type species of the highly speciose genus Galathea Fabricius, 1793 (Baba et al. 2008). The date of publication of Cancer strigosus is conventionally cited as 1761 (e.g., Baba et al. 2008: 78; Poore et al. 2011: xi). Evenhuis (1997: 478), however, showed that the publication in which the name Cancer strigosus was made available (i.e., Fauna Svecica sistens animalia Sveciae regni) was published before 14 November 1760. The date of publication of Cancer strigosus is therefore 1760.